Analisis Permasalahan Sampah Anorganik Di Pasar Sukaramai - Cindy Theresia Purba; Abigail linia Fanny Lahagu; Juni Simamora; Yordan Sihotang (Fakultas Teknik Universitas Cenderawasih, 2023)
Garbage is waste that is produced from human activities and has been no longer useful. Therefore, every city needs to have a final management site (TPA) so that waste in the market environment can be handled and managed into something useful such as crafts. This study used descriptive qualitative method. Determining informants used purposive sampling technique. Data collection techniques used were interviews, observation and documentation. The data validity criteria used are extending observations, increasing them persistence, and triangulation. The data analysis technique in this research uses reduction, display, verification. The research results show that the Pasar Sukaramai TPA has a special management site for plastic inorganic waste.